Molecular docking and pharmacophore models to probe binding hypothesis of inhibitors of hypoxia inducible factor-1. Issue 17 (22nd November 2022) - Rehman, Zaira; Jabeen, Ishrat; Fahim, Ammad; Bhatti, Attya; John, Peter
Abstract: Hypoxia inducible factor-1 is a heterodimeric transcription factor that regulates cellular responses to hypoxia and is involved in tumor progression and resistance to chemotherapy. Dimerization between HIF-1α and β subunits has been recognized crucial for DNA binding and transcriptional activity of HIF-1. Therefore, inhibitors of α and β dimerization subunits of HIF-1 may potentially evade HIF-1-mediated chemotherapy resistance. In the current study, ligand-based pharmacophore model was developed to determine 3 D binding features of HIF-1 inhibitors. The selected pharmacophore model comprises of one hydrogen bond donor, one hydrogen bond acceptor and one hydrophobic feature. The selected model was used for virtual screening of publically available data base by ChemBridge Corporation. Overall, six potential hits against HIF-1α and β dimerization have been identified. These include, Hit 1 (4-(4-chlorophenyl)-2, 6-dimethyl-3, 5-pyridinedicarboxylic acid), 3 (2-[2-(2-hydroxybenzoyl)carbonohydrazonoyl]benzoic acid) and 5 (3-(4-methoxyphenyl)-2, 4-quinolinedicarboxylic acid) nicotonic acid derivatives, Hit 2 (3-[(1-adamantylamino)sulfonyl]benzoic acid), 4 (5-[(2-fluorophenyl)amino]sulfonyl-2-methylbenzoic acid), and 6 (4-([2-(trifluoromethyl)phenyl]sulfonylamino)benzoic acid) sulfonamide derivatives. Additionally, adamantyl moiety of compound 2 shows interactions with the experimentally known hydrophobic amino acid residues (V336, C334, E245) of HIF-1α and β dimerization site. The identified hits showed lower to higher µM biological activity (IC50 ) values and thus, after further structure optimization may serve as potential inhibitor of HIF-1 dimerization in cancer chemotherapy. Communicated by Ramaswamy H. Sarma